2021
DOI: 10.1177/13607804211002841
|View full text |Cite
|
Sign up to set email alerts
|

Edgework, Uncertainty, and Social Character

Abstract: This article proposes a novel conceptual understanding of ‘edgework’ – a term denoting the voluntary embrace of risk – by drawing on the long-standing sociological tradition of character studies. In doing so, it addresses the paradox that while first-generation research into high-risk leisure suggested that these activities provided identity-affirming escapes from bureaucratised capitalism, second-generation writings argued that edgework exists in harmony with the norms of ‘risk societies’, raising questions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 61 publications
1
5
0
Order By: Relevance
“…Overall, I believe that the programme meets most of the Edgework criteria that were originally identified by Lyng (1990). The argument supports and extends previous research which has suggested that certain forms of work can provide a vehicle for Edgework (Kidder, 2006; Mellor & Shilling, 2021; Roth, 2015). I would argue that, looked at in totality, a particular form of Edgework can be identified from studying the Enhanced Interrogation programme, which I refer to as ‘Institutional Edgework’.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Overall, I believe that the programme meets most of the Edgework criteria that were originally identified by Lyng (1990). The argument supports and extends previous research which has suggested that certain forms of work can provide a vehicle for Edgework (Kidder, 2006; Mellor & Shilling, 2021; Roth, 2015). I would argue that, looked at in totality, a particular form of Edgework can be identified from studying the Enhanced Interrogation programme, which I refer to as ‘Institutional Edgework’.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, work, rather than being a solely enervating force, may sometimes be a venue through which Edgework activities occur (Kidder, 2006; Roth, 2015); in Lyng's (1990) terms, under certain circumstances institutions can be vehicles for impulsive action. Certain types of jobs may facilitate Edgework more easily than others (Mellor & Shilling, 2021).…”
Section: Edgeworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Other‐directedness may not be the only characterological form evident nowadays (Mellor & Shilling, 2021; Shilling & Mellor, 2021), but if its present incarnation is failing to connect people to society via a set of qualities shared with fellow citizens, it is worth ending our conclusion by returning to Kornhauser's (1959) warnings in The Politics of Mass Society . Kornhauser (1959, p. 330) expressed concern that societies bereft of sufficiently strong intermediary organizations exposed individuals to the mobilizing capacities of potentially extremist elite groups.…”
Section: Discussionmentioning
confidence: 98%
“…Multicultural education provides a foundation for bonding with one another as a social commitment design (Hayes et al, 2021;Sather et al, 2018;Schubert & Kolb, 2021). It aims to develop social participation in building integrative nuances between individuals or groups (Mellor & Shilling, 2021;Outhwaite, 2022). Multicultural education uses ethnic, cultural, or linguistic aspects to spread diverse values, indicating that the cultural aspects explored can form a society with social resilience, a form of social achievement (Ahn, 2020;Lee & Curtis, 2017;Tebeau, 2021).…”
Section: Introductionmentioning
confidence: 99%